Race in Consumer Research: Past, Present, and Future - Grier, Sonya A; Crockett, David; Johnson, Guillaume D; Thomas, Kevin D; Bradford, Tonya Williams (Journal of Consumer Research, 2024)
Abstract Race has been a market force in society for centuries. Still, the question of what constitutes focused and sustainable consumer research engagement with race remains opaque. We propose a guide for scholars and scholarship that extends the current canon of race in consumer research toward understanding race, racism, and related racial dynamics as foundational to global markets and central to consumer research efforts. We discuss the nature, relevance, and meaning of race for consumer research and offer a thematic framework that critically categorizes and synthesizes extant consumer research on race along the following dimensions: (1) racial structuring of consumption and consumer markets, (2) consumer navigation of racialized markets, and (3) consumer resistance and advocacy movements. We build on our discussion to guide future research that foregrounds racial dynamics in consumer research and offers impactful theoretical and practical contributions.